Preparation method of high-strength integrated carbon fiber composite flange pipe tee joint

CN122939129APending Publication Date: 2026-10-20JILIN INST OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611083378.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]针对现有技术的不足,本发明提供了一种高强度一体化碳纤维复合材料法兰管三通的制备方法,解决了现有技术中碳纤维法兰三通管件在制造时容易出现结构连接处开裂、内部残留孔隙多以及法兰密封面难以实现可靠装配密封的问题

Benefits of technology

1、本发明改善了三通管件在连接部位的受力状态并提高了结构的整体承载力。通过使用不同树脂含量的预浸布对直管段与法兰部分进行分区铺设,配合在直管段侧开口衔接段和法兰连接部位额外增加单向碳纤维预浸布进行梯度补强,这种铺设方式能给厚度变化较大的区域补充所需的树脂,同时让顺着受力方向铺贴的单向纤维去承担外部载荷。这样限制了树脂基体的变形,减少了连接界面处分层与开裂的情况。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the field of composite material molding technology and discloses a method for preparing a high-strength integrated carbon fiber composite flange tee, comprising: cleaning and polishing a metal mold; alternately laying carbon fiber prepregs with different resin contents in sections for straight pipe sections, branch pipe sections, and flange sections; adding unidirectional carbon fiber prepregs for gradient reinforcement at the side opening connection section and flange connection area; creating a closed cavity after mold closing and vacuuming, then placing it in an autoclave for integrated curing using a multi-stage heating and pressurizing process; after slow cooling and demolding, trimming, plasma surface modification of the flange sealing surface, and machining bolt holes. This invention, through differentiated prepreg sectional laying and local unidirectional reinforcement, combined with multi-stage curing control, reduces delamination and cracking at the pipe connection interface, lowers internal porosity, and improves the overall load-bearing capacity and assembly sealing performance of the tee fitting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite material molding technology, specifically to a method for preparing a high-strength integrated carbon fiber composite flange tee. Background Technology

[0002] Carbon fiber composites are lightweight and high-strength, making them commonly used in the manufacture of various piping systems. However, in the manufacture of tee fittings with flanges, the junctions of straight pipes, branch pipes, and flanges are complex in shape and vary significantly in thickness. Conventional uniform layup methods struggle to accommodate the varying resin content requirements of different areas, easily leading to insufficient resin or resin buildup at corners. Furthermore, tee fittings experience internal fluid pressure and external forces in different directions during use. Previous practices rarely incorporated specialized local reinforcement along the primary stress direction, causing stress concentration at shape transitions, potentially leading to internal layup cracking and affecting the fitting's load-bearing capacity.

[0003] During the heat curing of tee fittings, the volatiles produced by the reaction of air and resin within the material are difficult to expel. If conventional hot-pressing methods are used, improper control of heating and pressurization times can lead to premature resin curing, trapping these volatiles inside and resulting in numerous internal pores in the finished product. This can cause thermal stress cracks upon cooling. Furthermore, the finished carbon fiber flange sealing surface itself does not readily adhere, and the tool marks left by ordinary machining, combined with the material's inherent properties, make it difficult to achieve a leak-proof seal when assembling with other components. These manufacturing challenges limit the application of integrated carbon fiber flange tees in more demanding applications. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a method for preparing a high-strength integrated carbon fiber composite flange tee, which solves the problems of cracking at structural connections, numerous internal residual pores, and difficulty in achieving reliable assembly and sealing of the flange sealing surface in the manufacturing process of existing carbon fiber flange tee fittings.

[0005] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing a high-strength integrated carbon fiber composite flange tee, comprising the following steps: Clean and polish the inner surface of the metal mold; The main body is laid in a metal mold. Carbon fiber prepreg with a fiber mass content of 58% to 62% is used as the laying material for the middle section of the straight pipe and the middle section of the branch pipe of the flange tee. Carbon fiber prepreg with a fiber mass content of 58% to 65% is used as the laying material for the flange part of the flange tee. The materials are laid alternately. On this basis, reinforcement is carried out by laying unidirectional carbon fiber prepreg with a fiber mass content of 62% to 65% at the connection section of the straight pipe section (the connection between branch pipe 4 and main passage straight pipe 5), the connection between flange (second flange 2 and third flange 3) and straight pipe (main passage straight pipe 5), and the connection between flange (first flange 1) and branch pipe (branch pipe 4). Before mold closing, a closed cavity is made, and the metal mold is vacuumed. The vacuum degree is controlled between -105kPa and -95kPa, and the vacuuming time is 19 to 21 minutes. The metal mold is placed in an autoclave for heating and pressurization to form and solidify in one piece. A multi-stage heating process is used. Then, heating is stopped, and the cooling rate is controlled at 0.5 to 1.0 °C / min to cool the metal mold to room temperature. The solidified flange tee is demolded and trimmed, the flange sealing surface is plasma-modified, and the flange bolt holes are machined.

[0006] By adopting the above technical solution, due to the use of prepreg with differentiated resin content for zonal laying and local unidirectional cloth gradient reinforcement, combined with targeted vacuuming and multi-stage curing control, the overall structural load-bearing capacity of the tee fitting is improved, interface delamination is avoided, and internal porosity is reduced.

[0007] Regarding the specific molding mechanism, considering the stress characteristics of straight pipe sections and branch pipe sections bearing the main internal pressure of the pipeline, a prepreg with a content of 58%–62% is selected to maintain the necessary fiber volume fraction and ensure circumferential and axial stiffness. Correspondingly, for the flange section, due to its complex shape and varying thickness, a prepreg with a content of 58%–65% is used to supplement the matrix resin. In the subsequent heat and pressurization stage, the excess resin undergoes physical rheology along the fiber bundle gaps under pressure, thereby filling the internal space of the geometric corner at the flange root and suppressing the formation of insufficient resin defects.

[0008] Considering that the straight pipe section with side openings and the flange root are areas where structural continuity is interrupted, multiaxial stresses are superimposed at these locations. In this case, the unidirectional carbon fiber prepreg laid along the direction of the local principal stress plays a role. The single fiber filaments bear the local tensile and compressive loads, constrain the deformation of the matrix and prevent cracking, thus promoting the formation of an integrated structure of equal strength between the flange and the pipe body.

[0009] Before chemical curing, a negative pressure environment of -105 kPa to -95 kPa drives the diffusion and precipitation of free air and low-molecular-weight volatiles between the layers. The system then enters a two-stage curing and cross-linking process. In the initial heating stage, the resin matrix in the prepreg absorbs heat energy, increasing the thermal motion of molecular chain segments. The system viscosity decreases, entering the minimum viscosity window, and the liquid resin macroscopically flows and impregnates the carbon fiber multifilaments under external pressure. As the temperature continues to rise to the activation energy required for the curing reaction, a chemical reaction is triggered within the matrix. Active groups such as epoxy groups undergo ring-opening, producing nucleophilic addition or substitution reactions with the curing agent molecules. Linear polymer chains cross-link to form a three-dimensional network macromolecular structure, and the material system transforms from a highly elastic state to a glassy state, achieving the curing and shaping of the composite material. The final slow cooling process releases the internal residual thermal stress accumulated due to the difference in thermal expansion coefficients between the fiber and the resin.

[0010] Preferably, both the carbon fiber prepreg and the unidirectional carbon fiber prepreg are T300-3K carbon fiber prepreg. During the main laying process, the carbon fiber prepreg used as the laying material for the middle sections of straight pipes and branch pipes has a fiber mass content of 60%. The carbon fiber prepreg used as the laying material for the flange part has a fiber mass content of 62%.

[0011] By adopting the above technical solution, T300-3K carbon fiber has both mechanical stability and process drape. The resin content of the structural area and the connection area are distinguished by a ratio of 60% and 62%, which reduces the occurrence of resin enrichment or resin deficiency while ensuring the cross-sectional modulus.

[0012] Preferably, the side opening of the straight pipe section is the connection point between the branch pipe and the main straight pipe; An additional layer of unidirectional carbon fiber prepreg was laid, with a fiber mass content of 63%.

[0013] By adopting the above technical solution, and considering the stress state at the geometric intersection of the main pipe and the branch pipe, the 63% content of unidirectional fabric provides uniaxial tensile strength. The unidirectional fiber group, in conjunction with the corresponding resin matrix, establishes a transmission path for interlayer shear force.

[0014] Preferably, the metal mold is an integrally detachable metal mold for integrated molding structure; After cleaning the inner surface of the metal mold and before polishing, the process also includes sequentially applying a release agent and a release wax to the inner surface of the metal mold. Polishing specifically refers to polishing to a mirror-like state with a roughness Ra of 0.8 μm.

[0015] By adopting the above technical solution, the overall disassembled structure combined with the complex T-shaped shape enables demolding. The 0.8μm surface roughness smooths the microscopic surface of the mold, and combined with the physical isolation layer of the release agent and release wax, it alleviates the mechanical interlocking effect at the mold interface during the resin curing shrinkage stage, maintaining the smoothness of the product surface.

[0016] Preferably, when alternating the laying process, 0° / 90° and 45° / -45° prepregs are laid alternately to the designed thickness, with the fiber direction deviation controlled within ±2°, and each layer is compacted using a rolling tool during the laying process.

[0017] By adopting the above technical solution, the alternating arrangement of the four angles gives the structure quasi-isotropic mechanical characteristics in the plane, which can resist the circumferential tension and axial tensile force generated by the internal fluid.

[0018] The ±2° deviation control limits the nonlinear shear deformation of the material under load, and the interlayer rolling process removes accumulated air and establishes the initial interlayer adhesion structure.

[0019] Preferably, when creating a closed cavity, specifically after the lower mold is laid but before the mold is closed, sealing strips, breathable felt, and vacuum bags are used to create the closed cavity.

[0020] By adopting the above technical solution, a low flow resistance exhaust channel is established with the help of the breathable felt in the airtight isolation barrier, so that all areas of the structure surface are in a uniform pressure environment.

[0021] Preferably, the process parameters for vacuuming are: The laid metal mold is vacuumed using a vacuum pump, with the vacuum level controlled at -100 kPa for 20 minutes to completely remove residual air and low-molecular-weight volatiles between layers.

[0022] By adopting the above technical solution, a venting pressure difference was established under the condition of -100kPa and 20 minutes, which caused volatile substances in the deep layers to escape to the outside of the structure before the viscosity of the resin system increased.

[0023] Preferably, when performing integrated heating and pressurization molding and curing, the metal mold is placed in a room temperature autoclave; The specific parameters for the multi-stage heating process are as follows: The first stage involves raising the temperature to 88–92°C at a rate of 2.0–2.4°C / min and maintaining it at a pressure of 240–260 kPa for 1.9–2.1 hours. In the second stage, the temperature is increased to 128–132°C at a rate of 0.8–1.2°C / min and maintained at a pressure of 590–610 kPa for 3.9–4.1 hours.

[0024] By adopting the above technical solution, the temperature rise rate is controlled in the first heating stage to reduce the temperature gradient difference inside and outside the layup, and the resin is kept at a low viscosity state by maintaining the temperature at 88-92℃. Under a pressure of 240-260kPa, the liquid resin is forced to expel bubbles and penetrate into the fiber bundle gaps. In the second stage, the heating rate is slowed down to enter the polymerization range of 128-132℃, and combined with a pressure of 590-610kPa, the microcracks caused by the concentrated exothermic reaction of chemical cross-linking are suppressed, so that the polymer network structure is densely formed.

[0025] The preferred parameters for the multi-stage heating process are as follows: The first stage involves heating to 90℃ at a rate of 2.0℃ / min and maintaining the temperature at 250kPa for 2.0 hours. In the second stage, the temperature is increased to 130℃ at a heating rate of 1.0℃ / min and maintained at 600kPa pressure for 4.0 hours.

[0026] The preferred method for demolding and trimming is as follows: Use cutting tools to trim the edges, side openings, and flange connection surfaces of the flange pipe tee, and then polish the surfaces with 200-grit, 400-grit, and 600-grit sandpaper in sequence. Before machining the flange bolt holes, plasma surface modification of the flange sealing surface is also included.

[0027] By employing the above technical solution, gradient sandpaper polishing removes stress concentration areas left by macroscopic cutting. After plasma treatment, particles bombard the solidified material surface and break some of the macromolecular backbone, introducing polar oxygen-containing functional groups into the surface and changing the surface free energy state, thereby improving the sealing reliability of subsequent assembly and connection interfaces.

[0028] This invention provides a method for preparing a high-strength integrated carbon fiber composite flange tee. It has the following beneficial effects: 1. This invention improves the stress state at the connection points of tee pipe fittings and enhances the overall load-bearing capacity of the structure. By using prepregs with different resin contents to lay in sections for the straight pipe section and flange, and by adding additional unidirectional carbon fiber prepregs at the side openings of the straight pipe section and the flange connection points for gradient reinforcement, this laying method can replenish the necessary resin to areas with large thickness variations, while allowing the unidirectional fibers laid in the direction of stress to bear the external load. This limits the deformation of the resin matrix and reduces delamination and cracking at the connection interface.

[0029] 2. This invention reduces the porosity of the composite material and improves the structural density of the pipe fitting. By creating a closed cavity and performing vacuum treatment before mold closing, combined with a multi-stage heating and pressurizing curing process, residual air and volatiles between layers are dissipated when the resin is at a low viscosity stage. Subsequent stepped heating and pressurizing operations control the heat generation process during resin curing, reducing the formation of internal bubbles and thermal stress microcracks, and controlling the porosity of the finished product to less than one percent.

[0030] 3. This invention optimizes the appearance molding quality and interface assembly sealing performance of flange tees. Utilizing an integrally disassembled metal mold with a polished roughness of 0.8μm, combined with the isolation effect of the release medium, it alleviates the problem of resin shrinkage during curing causing sticking to the mold surface and hindering demolding, ensuring the integrity of demolding complex shapes. In subsequent processing, plasma is used to modify the flange sealing surface, introducing polar oxygen-containing functional groups into the material surface, altering the surface physicochemical state of this region, and laying the material foundation for subsequent assembly sealing at the flange connection. Attached Figure Description

[0031] Figure 1 This is a diagram showing the measured mass and apparent density distribution of the flange tee of the present invention; Figure 2 The diagrams show the test results of the airtightness and ultimate pressure bearing performance of the flange tee of the present invention, wherein (a) is a helium leakage rate distribution diagram; and (b) is a distribution diagram of the ultimate burst pressure. Figure 3 The figures show a comparison of the dynamic vibration fatigue performance of the flange tee of the present invention, wherein (a) is a comparison of the initial dynamic stiffness; and (b) is a comparison of the cantilever vibration fatigue life. Figure 4 The following are test diagrams of the thermal shock performance of the flange tee of the present invention, wherein (a) is a distribution diagram of the change rate of flange outer diameter after thermal shock of each test object; and (b) is a distribution diagram of residual interlaminar shear strength after thermal shock of each test object. Figure 5 The diagram shows the distribution of impact damage area and residual blast pressure after impact in this invention. (a) is the distribution of impact damage area by ultrasonic C-scan for each experimental object; (b) is the distribution of residual blast pressure after impact for each experimental object.

[0032] Figure 6 This is a schematic diagram of the carbon fiber flange tee of the present invention.

[0033] In the diagram: 1. First flange; 2. Second flange; 3. Third flange; 4. Branch pipe; 5. Main passage straight pipe. Detailed Implementation

[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0035] It should be noted that the specific embodiments described below all use T300-3K carbon fiber prepreg as a specific example of the laying material. However, those skilled in the art should understand that the technical solutions and process control principles of the present invention are also applicable to other grades, strength levels (such as but not limited to T700, T800, T1000 series high-strength / high-modulus carbon fibers) or different tow specifications (such as 1K, 12K, etc.) of carbon fiber prepreg materials.

[0036] Examples 1-4: Example 1: This embodiment provides a method for preparing a high-strength integrated carbon fiber composite flange tee, including the following steps: Prepare an integrally detachable metal mold for the integrated molding structure, clean the inner surface of the mold, and apply mold release agent and mold release wax in sequence, polishing to a mirror finish with a roughness Ra of 0.8μm; The main body is laid in the mold. T300-3K carbon fiber prepreg with a fiber mass content of 60% is used as the laying material for the middle section of the straight pipe and the middle section of the branch pipe. T300-3K carbon fiber prepreg with a fiber mass content of 62% is used as the laying material for the flange part. 0° / 90° and 45° / -45° prepreg are laid alternately to the design thickness. The fiber direction deviation is controlled within ±2°. Each layer is compacted with a rolling tool during the laying process. like Figure 6 As shown, reinforcement is carried out on this basis. At the connection section of the straight pipe section (the connection between branch pipe 4 and main passage straight pipe 5), the connection between flange (second flange 2 and third flange 3) and straight pipe (main passage straight pipe 5), and the connection between flange (first flange 1) and branch pipe (branch pipe 4), an additional layer of unidirectional T300-3K carbon fiber prepreg with a fiber mass content of 63% is laid for gradient reinforcement. After the lower mold is laid, before closing the mold, use sealing strips, breathable felt and vacuum bags to make a closed cavity. Use a vacuum pump to vacuum the laid mold, control the vacuum degree at -100kPa, and vacuum for 20 minutes to completely remove residual air and low molecular weight volatiles between the layers. The assembled mold is placed in a room temperature autoclave for heating and pressurization to form and solidify the mold in one piece. A multi-stage heating process is adopted. In the first stage, the temperature is raised to 90°C at a heating rate of 2.0°C / min and held at 250 kPa pressure for 2.0 hours. In the second stage, the temperature is raised to 130°C at a heating rate of 1.0°C / min and held at 600 kPa pressure for 4.0 hours. Then the heating is stopped and the cooling rate is controlled at 0.5 to 1.0°C / min to cool the metal mold to room temperature. The solidified tee is demolded, and the edges, side openings and flange connection surfaces of the tee are trimmed with high-precision cutting tools. The surfaces are then polished with 200-grit, 400-grit and 600-grit sandpaper in sequence. The flange sealing surface is subjected to plasma surface modification. The flange bolt holes are machined and the hole position accuracy is ensured to produce the finished product. The internal porosity of the finished product is tested to be ≤1%.

[0037] Example 2: This embodiment provides a method for preparing a high-strength integrated carbon fiber composite flange tee, including the following steps: Prepare an integrally detachable metal mold for the integrated molding structure, clean the inner surface of the mold, and apply mold release agent and mold release wax in sequence, polishing to a mirror finish with a roughness Ra of 0.8μm; The main body is laid in the mold. T300-3K carbon fiber prepreg with a fiber mass content of 58% is used as the laying material for the middle section of the straight pipe and the middle section of the branch pipe. T300-3K carbon fiber prepreg with a fiber mass content of 58% is used as the laying material for the flange part. 0° / 90° and 45° / -45° prepreg are laid alternately to the design thickness. The fiber direction deviation is controlled within ±2°. Each layer is compacted with a rolling tool during the laying process. On this basis, reinforcement is carried out by laying an additional layer of unidirectional T300-3K carbon fiber prepreg with a fiber mass content of 62% at the connection section of the straight pipe section (the connection between branch pipe 4 and main passage straight pipe 5), the connection between flange (second flange 2 and third flange 3) and straight pipe (main passage straight pipe 5), and the connection between flange (first flange 1) and branch pipe (branch pipe 4). After the lower mold is laid, before closing the mold, use sealing strips, breathable felt and vacuum bags to make a closed cavity. Use a vacuum pump to vacuum the laid mold, control the vacuum degree at -95kPa, and vacuum for 19 minutes to completely remove residual air and low molecular weight volatiles between the layers. The assembled mold is placed in a room temperature autoclave for heating and pressurization to form and cure in one piece. A multi-stage heating process is adopted. In the first stage, the temperature is raised to 88°C at a heating rate of 2.0°C / min and held at 240kPa pressure for 1.9 hours. In the second stage, the temperature is raised to 128°C at a heating rate of 0.8°C / min and held at 590kPa pressure for 3.9 hours. Then the heating is stopped and the mold is slowly cooled to room temperature with the equipment. The solidified tee is demolded, and the edges, side openings and flange connection surfaces of the tee are trimmed with high-precision cutting tools. The surfaces are then polished with 200-grit, 400-grit and 600-grit sandpaper in sequence. The flange sealing surface is subjected to plasma surface modification. The flange bolt holes are machined and the hole position accuracy is ensured to produce the finished product. The internal porosity of the finished product is tested to be ≤1%.

[0038] Example 3: This embodiment provides a method for preparing a high-strength integrated carbon fiber composite flange tee, including the following steps: Prepare an integrally detachable metal mold for the integrated molding structure, clean the inner surface of the mold, and apply mold release agent and mold release wax in sequence, polishing to a mirror finish with a roughness Ra of 0.8μm; The main body is laid in the mold. T300-3K carbon fiber prepreg with a fiber mass content of 62% is used as the laying material for the middle section of the straight pipe and the middle section of the branch pipe. T300-3K carbon fiber prepreg with a fiber mass content of 65% is used as the laying material for the flange part. 0° / 90° and 45° / -45° prepreg are laid alternately to the design thickness. The fiber direction deviation is controlled within ±2°. Each layer is compacted with a rolling tool during the laying process. On this basis, reinforcement is carried out by laying an additional layer of unidirectional T300-3K carbon fiber prepreg with a fiber mass content of 65% at the connection section of the straight pipe section (the connection between branch pipe 4 and main passage straight pipe 5), the connection between flange (second flange 2 and third flange 3) and straight pipe (main passage straight pipe 5), and the connection between flange (first flange 1) and branch pipe (branch pipe 4). After the lower mold is laid, before closing the mold, use sealing strips, breathable felt and vacuum bags to make a closed cavity. Use a vacuum pump to vacuum the laid mold, control the vacuum degree at -105kPa, and vacuum for 21 minutes to completely remove residual air and low molecular weight volatiles between the layers. The assembled mold is placed in a room temperature autoclave for heating and pressurization to form and cure in one piece. A multi-stage heating process is adopted. In the first stage, the temperature is raised to 92°C at a heating rate of 2.4°C / min and held at 260kPa pressure for 2.1 hours. In the second stage, the temperature is raised to 132°C at a heating rate of 1.2°C / min and held at 610kPa pressure for 4.1 hours. Then the heating is stopped and the mold is slowly cooled to room temperature with the equipment. The solidified tee is demolded, and the edges, side openings and flange connection surfaces of the tee are trimmed with high-precision cutting tools. The surfaces are then polished with 200-grit, 400-grit and 600-grit sandpaper in sequence. The flange sealing surface is subjected to plasma surface modification. The flange bolt holes are machined and the hole position accuracy is ensured to produce the finished product. The internal porosity of the finished product is tested to be ≤1%.

[0039] Example 4: This embodiment provides a method for preparing a high-strength integrated carbon fiber composite flange tee, including the following steps: Prepare an integrally detachable metal mold for the integrated molding structure, clean the inner surface of the mold, and apply mold release agent and mold release wax in sequence, polishing to a mirror finish with a roughness Ra of 0.8μm; The main body is laid in the mold. T300-3K carbon fiber prepreg with a fiber mass content of 58% is used as the laying material for the middle section of the straight pipe and the middle section of the branch pipe. T300-3K carbon fiber prepreg with a fiber mass content of 60% is used as the laying material for the flange part. 0° / 90° and 45° / -45° prepreg are laid alternately to the design thickness. The fiber direction deviation is controlled within ±2°. Each layer is compacted with a rolling tool during the laying process. On this basis, reinforcement is carried out by laying an additional layer of unidirectional T300-3K carbon fiber prepreg with a fiber mass content of 63% at the connection section of the straight pipe section (the connection between branch pipe 4 and main passage straight pipe 5), the connection between flange (second flange 2 and third flange 3) and straight pipe (main passage straight pipe 5), and the connection between flange (first flange 1) and branch pipe (branch pipe 4). After the lower mold is laid, before closing the mold, use sealing strips, breathable felt and vacuum bags to make a closed cavity. Use a vacuum pump to vacuum the laid mold, control the vacuum degree at -102kPa, and vacuum for 20 minutes to completely remove residual air and low molecular weight volatiles between the layers. The assembled mold is placed in a room temperature autoclave for heating and pressurization to form and cure in one piece. A multi-stage heating process is adopted. In the first stage, the temperature is raised to 91°C at a heating rate of 2.2°C / min and held at 255 kPa pressure for 2.0 hours. In the second stage, the temperature is raised to 131°C at a heating rate of 1.1°C / min and held at 605 kPa pressure for 4.0 hours. Then the heating is stopped and the mold is slowly cooled to room temperature with the equipment. The solidified tee is demolded, and the edges, side openings and flange connection surfaces of the tee are trimmed with high-precision cutting tools. The surfaces are then polished with 200-grit, 400-grit and 600-grit sandpaper in sequence. The flange sealing surface is subjected to plasma surface modification. The flange bolt holes are machined and the hole position accuracy is ensured to produce the finished product. The internal porosity of the finished product is tested to be ≤1%.

[0040] Comparative Examples 1-5: Comparative Example 1: Compared with Example 1, the difference lies in the molding process. This comparative example adopts a traditional split molding process, that is, firstly, a complete main channel straight pipe section is prepared using a mold and cured, then mechanically opening holes on the side of the straight pipe to cut off the original continuous carbon fiber structure, and finally using structural adhesive to bond and assemble the separately molded and cured branch pipes and flanges to the opening and both ends of the straight pipe. The proportions and curing parameters of the remaining lay-up materials are the same, and the finished product has stress concentration points at the edge of the opening.

[0041] Comparative Example 2: Compared with Example 1, the difference lies in the autoclave curing process. This comparative example omits the first stage of low-temperature and low-pressure leveling. After the assembled mold is placed in the autoclave, it is directly heated to 130°C at a heating rate of 2.0°C / min and maintained at a high pressure of 600 kPa for 6 hours for single-stage high-temperature and high-pressure crosslinking curing. All other aspects are the same. Obvious uneven resin distribution and micropores were detected inside the finished product.

[0042] Comparative Example 3: Compared with Example 1, the difference lies in the parameters of the vacuuming step. In this comparative example, after the tiling is completed and the mold is closed, the vacuum degree of the vacuum pump is only controlled at -50kPa (that is, the absolute value of the negative pressure does not reach the specified range of -95kPa to -105kPa). All other parameters are the same, resulting in the porosity of the final cured part being greater than 1%.

[0043] Comparative Example 4: Compared with Example 1, the difference is that no precise reinforcement was carried out during the laying and molding stage. In this comparative example, T300-3K carbon fiber prepreg with a fiber mass content of 60% was used for uniform global laying with the same thickness throughout the entire mold cavity (including all straight pipe sections, branch pipe sections, connecting sections and flange areas). No additional unidirectional carbon fiber prepreg was laid for local reinforcement at the side opening connecting sections of straight pipe sections and the connection between flanges and straight pipes. All other aspects are the same.

[0044] Comparative Example 5: Compared with Example 1, the difference is that no gradient material distribution was carried out in the laying and molding stage. In order to pursue the highest overall strength, this comparative example used T300-3K carbon fiber prepreg with a fiber mass content of 65% in all areas (including low stress areas such as the middle section of the straight pipe and high stress areas). The resin proportion was not appropriately increased in the low stress area, and the rest were the same. Although the strength met the standard, the overall weight of the component increased significantly, and the lightweight requirements were not met.

[0045] Test Examples 1-5: Test Example 1: This experiment measures the macroscopic physical properties and lightweight indexes of the high-strength integrated carbon fiber composite flange tees prepared in Examples 1 to 4.

[0046] The surfaces of each flange and tee sample after demolding were wiped with anhydrous ethanol to remove any residual release wax and dust. Then, all samples were placed in a 60°C forced-air drying oven for 4 hours to eliminate the interference of ambient humidity on the initial quality. After drying, the samples were placed in a desiccator to cool to room temperature.

[0047] The absolute mass of each group of samples was repeatedly weighed three times using an industrial-grade precision electronic balance with a range of 3000g and an accuracy of 0.1g. The arithmetic mean of the weighings was taken as the measured dry weight of the components in that group and recorded.

[0048] Due to the complex internal cavity and side opening structure of flanged pipe tees, conventional geometric measurement methods have significant errors. Therefore, the experiment used the pure water displacement method to determine its drainage volume. To prevent water molecules from penetrating the surface micropores, an extremely thin waterproof polyurethane film was vacuum-sealed over the entire component before measurement. The volume of the film itself was known and deducted from the calculation. The coated sample was completely immersed in a constant-volume overflow tank containing deionized water. The mass of the overflowing water was collected and weighed, and the measured volume of the component was calculated using the density of water at that temperature. The apparent density of each sample was calculated by dividing the measured mass by the measured volume.

[0049] Table 1. Macroscopic physical properties and lightweight test data of Examples 1-4 Summarize: Figure 1 These are test results of macroscopic physical performance indicators of Embodiments 1 to 4 of the present invention. Figure 1 The left vertical axis and the black solid line and circular marker represent the measured mass distribution of each embodiment, the right vertical axis and the gray dashed line and square marker represent the calculated apparent density of the corresponding embodiment, and the horizontal axis corresponds to the four independent experimental objects.

[0050] According to Table 1 and Figure 1 According to the data, the measured volume of each embodiment remained between 1255 and 1262 cm³. 3 Within this range, the consistency of these dimensions reflects the stability of the rigid molded volume; therefore, fluctuations in the measured mass of the component are mainly caused by differences in the ratio of internal fiber to resin material. In Example 3, due to the high fiber content throughout the entire region, its overall apparent density reaches 1.589 g / cm³. 3 The measured weight of a single component was 1994.8g. In practical applications, simply increasing the fiber content would increase the weight of the component. For pipeline systems with weight reduction requirements, this material distribution method needs to be optimized. Example 2 had a lower total weight of 1869.5g, with its density reduced to 1.482g / cm³. 3 This indicates that the resin matrix accounts for a larger proportion under low fiber content processes.

[0051] Example 4 adjusted the flange area proportions, and its measured mass and apparent density were 1903.5 g and 1.511 g / cm³, respectively. 3 The quality is somewhat reduced. Observing the data from Example 1, it can be found that when a gradient material distribution is used for the straight pipe section and flange connection area, the apparent density of the component is 1.537 g / cm³. 3 The overall measured weight is 1934.6g. This method of increasing carbon fiber in local high-stress areas while appropriately reducing fiber and increasing resin ratio in low-stress sections avoids the extra weight increase caused by increasing the overall thickness.

[0052] The apparent densities of all embodiments conform to the standard range for composite materials, indicating that the multi-stage autoclave curing process can reduce internal porosity. This is because the pressure and temperature in the first stage cause the resin to expel air between the fiber bundles while in a flowing state, resulting in a more compact structure after molding. The internal porosity of the finished product is strictly controlled below 1%, reducing the probability of low density caused by air retention. This demonstrates that by adjusting the material ratio and controlling the curing process, the overall weight of the component can be controlled while meeting molding requirements and achieving lightweight goals.

[0053] Test Example 2: This experiment conducts non-destructive tests on the airtightness and ultimate pressure bearing capacity of the high-strength integrated carbon fiber composite flange tees prepared in Examples 1 to 4.

[0054] The experimental samples require interface sealing treatment. The flange tee is fixed to a dedicated pressure testing bench. Using a stainless steel blind flange plate and butyl rubber gasket, the two open ends of the sample are mechanically sealed with a torque wrench, leaving one straight pipe end flange as the interface for fluid injection and pressure monitoring.

[0055] Static helium mass spectrometry leak detection was performed. High-purity helium was injected into the pipe fitting through the reserved interface, and the pressure was slowly increased to the set pressure of 2.5 MPa and held for 30 minutes. A suction-type helium mass spectrometer was used to scan the entire area along the outer surface of the pipe fitting, each flange joint, and the transition section of the branch pipe. The local leakage rate at each monitoring point was recorded, and the highest value during the pressure holding period was taken as the overall helium leakage rate of the sample.

[0056] After purging the helium and replacing the air inside the tube, a destructive hydrostatic burst test was conducted. Deionized water was continuously injected into the tube until it overflowed, and the system was sealed after purging any remaining air. A high-pressure plunger pump was started, and the tube was pressurized in stages at a constant rate of 0.5 MPa / s. When a macroscopic rupture occurred in the tube wall, causing a sudden drop in internal pressure, the peak pressure captured by the hydraulic sensor was recorded as the ultimate burst pressure of the sample.

[0057] Table 2. Non-destructive airtightness and ultimate pressure test data of Examples 1-4 Summarize: Figure 2 (a) The black solid line and the upper triangle mark represent the leakage rate values ​​of each experimental subject; Figure 2 (b) The black dotted lines and diamond marks represent the burst pressure values ​​of the corresponding samples, and the horizontal axis corresponds to the four independent experimental objects.

[0058] According to Table 2 and Figure 2 According to the data, the helium leakage rate in Example 3 was 4.12 × 10⁻⁶. -6 Pa·m 3 The leakage rate was / s, which was relatively high among the four sample groups. The airtightness of composite pipe fittings generally depends on the degree of resin filling the fiber gaps and internal interlayers. Example 3 had a high fiber content and a relatively low resin content, resulting in incomplete closure of internal micropores. Gas permeated outwards along the incompletely wetted fiber gaps, leading to a higher measured leakage rate. Due to the influence of internal micropores, its water pressure burst pressure was 27.1 MPa, indicating that simply increasing the fiber content did not result in the highest pressure resistance. The leakage rate of Example 2 was 0.89 × 10⁻⁶. - 6 Pa·m 3 / s. This group of samples had a relatively low fiber content and a high resin content. The abundant resin flowed fully during the molding and heating stage, sealing potential leakage channels. In the water pressure ultimate burst test, Example 2's burst pressure was 24.6 MPa. This indicates that the reduced carbon fiber content decreased the pipe's ability to resist internal pressure, causing the pipe wall to fracture at a lower pressure. Example 4 adjusted the material ratio in the flange area, and the measured helium leakage rate was 1.98 × 10⁻⁶. -6 Pa·m 3 / s, burst pressure is 26.8MPa, and all test indicators are between the two groups mentioned above. In Example 1, a higher proportion of carbon fiber is used in stress concentration areas such as side branches and flanges to withstand tensile stress, while a moderate resin content is used in the middle section of the straight pipe to maintain the airtightness of the structure.

[0059] The burst pressure measured by this group was 28.3 MPa, and the leakage rate was controlled at 1.45 × 10⁻⁶. -6 Pa·m 3 / s. During the test, no delamination sound was observed in the pipe fitting before failure, indicating that the temperature and pressure parameters of the multi-stage curing process were effective. The initial heat preservation stage allowed the resin to penetrate and expel gases and low-molecular-weight volatiles at a low viscosity. The subsequent temperature and pressure increases promoted resin cross-linking and curing, resulting in a tighter bond between the fibers and the resin matrix, effectively controlling porosity. Combined with the various indicators, it can be seen that using different material ratios in different areas can achieve a good balance between improving structural load-bearing capacity and ensuring airtightness.

[0060] Test Example 3: This experiment compares the cantilever dynamic vibration fatigue life of the carbon fiber composite flange tees prepared in Example 1 and Comparative Examples 1 to 3.

[0061] The experimental samples were not specially coated and remained in their original state after demolding. The flanges at both ends of the main straight pipe section of the flange tee were placed flat on a cast iron rigid test bench with T-slots. The main straight pipe section was fixed in place using custom-made U-shaped high-strength bolts and pressure plates, so that the side branch pipe was in a horizontal cantilever state, serving as the test object for subsequent loading.

[0062] A loading connecting rod is inserted into the center hole of the end flange of the side branch pipe and connected to the excitation head of the electromagnetic vibration table below. A dynamic force sensor is installed in series between the excitation head and the connecting rod, and a uniaxial accelerometer is arranged on the outside of the branch pipe flange to collect the input load and the response displacement at the end in real time.

[0063] A sinusoidal waveform was used for reciprocating alternating displacement loading, with the loading frequency set at 15Hz to avoid the component's natural resonant frequency, and the displacement amplitude controlled within ±4.5mm. After the test started, the control system recorded the load and displacement data for each cycle in real time and calculated the dynamic stiffness of the component.

[0064] When the real-time dynamic stiffness of the component drops to 80% of its initial dynamic stiffness, or when structural damage phenomena such as macroscopic cracking, breakage, or detachment of the pipe are observed, the equipment automatically shuts down. The total number of cyclic loading cycles at the time of shutdown is recorded as the cantilever dynamic vibration fatigue life of the sample.

[0065] Table 3. Dynamic vibration fatigue performance test data of Example 1 and Comparative Examples 1-3 Summarize: Figure 3 (a) The black solid line and asterisk mark represent the initial stiffness values ​​of each experimental object; Figure 3 (b) The black dashed line and pentagram mark represent the fatigue cycle life of the corresponding sample, and the horizontal axis corresponds to the four independent experimental objects.

[0066] According to Table 3 and Figure 3 The data shows that Comparative Example 1 had a vibration fatigue life of 42,109 cycles and an initial dynamic stiffness of 11.84 kN / mm, which was the lowest among the four samples. In pipeline systems subjected to reciprocating pump vibrations, fatigue failure typically originates in areas where material continuity is disrupted. Comparative Example 1 employed a process of separate processing followed by bonding, where openings on the straight pipe side physically severed the original carbon fiber bundles, leaving stress transfer between the branch pipe and the straight pipe reliant solely on epoxy structural adhesive. This resin-based bonding interface is prone to localized stress concentration points under alternating bending moments, leading to the initiation and gradual propagation of microcracks in the adhesive layer, resulting in premature component failure. Example 1 achieved an initial dynamic stiffness of 14.23 kN / mm and a fatigue life of 284,512 cycles. This improved load-bearing capacity is related to the integrated co-curing mechanism. By overlapping the prepregs in each part before curing and cross-linking, the carbon fiber filaments maintained continuous morphological extension across the various geometric surfaces of the tee. When the component is subjected to cyclic loads, the alternating stress is channeled along the continuous fiber skeleton, which alleviates the geometric abrupt changes and local load peaks caused by the bonding process.

[0067] Analysis of the data from Comparative Examples 2 and 3 reveals that even with a monolithic molding process, deviations in thermodynamic curing parameters still affect stiffness and fatigue life. Comparative Example 2 omitted the first stage of low-temperature, low-pressure leveling; its initial dynamic stiffness was 13.51 kN / mm, and its fatigue life was 135,488 cycles. This indicates that if the resin fails to fully impregnate the carbon fibers at low viscosity, resin residues and micropores will remain in the cross-linked matrix, resulting in significant uneven resin distribution.

[0068] These fiber regions not encapsulated by the matrix are prone to frictional damage under vibration loads, evolving into initiation points for fatigue cracks. Comparative Example 3, due to insufficient vacuum, had an initial dynamic stiffness of 12.97 kN / mm and a test life of 176,923 cycles. The low negative pressure made it difficult to completely remove air introduced between the layers, and the resulting porosity defects reduced the interlayer bonding strength of the composite material, directly related to the fact that the porosity of this group of samples was greater than 1%. The distribution characteristics of the test data indicate that the continuous fiber laying plan and the process parameters of the multi-stage autoclave venting are interconnected; both are necessary to ensure the long-term service stability of the integrated composite component under dynamic conditions.

[0069] Test Example 4: This experiment tested the carbon fiber composite flange tees prepared in Example 1 and Comparative Examples 1 to 3 under high and low temperature alternating thermal shock and residual interlaminar shear strength.

[0070] Before the experiment, the flange tee samples of Example 1 and Comparative Examples 1 to 3 were placed on the experimental table and their surfaces were cleaned. The outer diameter of the straight flange of each sample was measured at multiple points using a coordinate measuring machine, and the initial reference dimensions were recorded. To establish a comparative reference, standard specimens were cut from the transition area of ​​the spare branch pipe of the same batch of samples in each group of samples, and the initial interlaminar shear strength was determined using a universal testing machine.

[0071] The test samples were transferred to a programmable high and low temperature alternating test chamber. The temperature range of the cycling environment was set from -40℃ to +120℃. The residence time of the sample at the high and low temperature extreme points in a single cycle was set to 1 hour, and the heating and cooling rate in the high and low temperature transition range was controlled at more than 10℃ / min. The equipment was started and continuously run for 100 thermal shock cycles.

[0072] After the cyclic loading was completed, all pipe fitting samples were removed and placed at room temperature (25±2℃, relative humidity 50%) for 24 hours. The outer diameter of the straight pipe flange was measured again using a coordinate measuring machine, and the measured data was compared with the initial reference dimensions to calculate the dimensional change rate before and after the thermal shock.

[0073] Long strip specimens were cut from the transition zone of the pipe branch after thermal shock using a water-cooled diamond cutter. The specimens were placed on the three-point bending loading fixture of a universal testing machine, and a compressive load was applied downward at a constant rate of 2.0 mm / min. The peak load at which the specimens failed under interlaminar shear was recorded, and the residual interlaminar shear strength of each specimen was calculated according to standard specifications.

[0074] Table 4. High and low temperature alternating thermal shock test data of Example 1 and Comparative Examples 1-3 Summarize: Figure 4 (a) The black solid line and the downward triangle mark represent the numerical values ​​of the rate of change of size of each experimental object; Figure 4 (b) The black dotted line and the right-pointing triangle mark represent the shear strength values ​​of the corresponding samples, and the horizontal axis corresponds to the four independent experimental objects.

[0075] According to Table 4 and Figure 4 The data shows that the flange outer diameter change rate of Comparative Example 1 was 0.417%, and the residual interlaminar shear strength was 21.27 MPa. These two figures represent the largest dimensional changes and lowest mechanical strengths among all test groups. In actual pipeline system operation, the periodic alternation of ambient temperature can cause deformation incompatibility between the material matrix and reinforcement. The axial thermal expansion coefficient of carbon fiber is typically close to zero or even negative, while the epoxy resin matrix exhibits positive thermal expansion characteristics. The pipe fitting in Comparative Example 1 was assembled by secondary bonding of two processed parts, with the adhesive layer at the bonding interface mainly composed of pure resin. When the sample repeatedly switched between high and low temperatures, mismatched volume shrinkage and expansion stresses occurred at the interface between the structural adhesive layer and the carbon fiber composite material.

[0076] This accumulated thermal stress concentrates at the connection nodes, causing microcracks to initiate within the adhesive layer and propagate outwards, weakening the overall dimensional stability and shear load-bearing capacity of the pipe fitting. The test results of Example 1 differ from those of the traditional process, with a dimensional change rate of 0.082% and a residual interlaminar shear strength of 48.64 MPa. The integrated co-curing process maintains the physical extension of the continuous carbon fiber bundles between different branches of the pipe fitting, and the resin matrix cross-links within the fiber skeleton to form a uniform network structure, mitigating the gradient of thermal expansion coefficients within the composite material. The unbalanced stress caused by temperature fluctuations is borne and dispersed by the continuously distributed fibers, preventing fatigue cracking at the matrix interface.

[0077] Analysis of the data from Comparative Examples 2 and 3 reveals that the setting of process parameters has a specific impact on the material's ability to resist alternating temperature environments. Comparative Example 2 omitted the low-temperature leveling process in the early curing stage; its measured residual interlaminar shear strength was 35.81 MPa, corresponding to a flange outer diameter change rate of 0.265%. Because the high-viscosity resin failed to fully penetrate the fiber layer, the dry spots remaining inside the pipe fitting were prone to interlaminar delamination under the physical drive of thermal expansion and contraction. The uneven micro-stress within the material led to a decrease in macroscopic mechanical strength.

[0078] Comparative Example 3, due to inadequate vacuuming process, exhibited a dimensional change rate of 0.312%, with a measured residual interlaminar shear strength of 32.39 MPa. The trace amounts of air entangled between the layers (leading to higher internal porosity) expanded during the high-temperature phase of thermal shock, generating minute internal compressive stress on the surrounding cured resin, and subsequently contracted during the low-temperature phase. This alternating air pressure at the microscale is equivalent to applying a continuous fatigue load to the composite material, disrupting the bond between the fiber and resin. All experimental data collectively indicate that the density at the material's microscopic level determines the upper limit of the component's resistance to alternating environmental stress. The multi-stage autoclave process not only eliminates internal voids through the venting mechanism but also promotes more stable cross-linking and rearrangement of the resin molecular chains within a specific temperature range. This internal material state, constrained by the process specifications, ensures the performance of the composite component under complex temperature fields.

[0079] Test Example 5: This experiment conducted low-speed drop hammer impact and residual burst pressure tests on the carbon fiber composite flange tees prepared in Example 1 and Comparative Examples 1 to 3 to evaluate the damage tolerance and safe pressure margin of composite pipe fittings after encountering external mechanical collisions.

[0080] The flange tee samples from Example 1 and Comparative Examples 1 to 3 were fixed on a custom-made V-shaped rigid support test bench. Mechanical clamps were used to lock both ends of the straight pipe flange to prevent horizontal displacement during the test. The transition area where the side branch pipe meets the main straight pipe was selected as the target point for the impact test. The initial wall thickness of the target area was recorded using a micrometer, and the impact center point was marked.

[0081] A drop hammer impact testing machine was used to vertically load the samples. A 16mm diameter hemispherical precision steel punch was selected, and the total impact energy of the drop hammer was set to 30J based on the common working condition of accidental tool drops in engineering. The drop hammer was released to perform a single impact on the target area of ​​each pipe fitting, and the system simultaneously collected the load-displacement transient data during the impact process.

[0082] After the impact test, the sample is transferred to a water immersion ultrasonic C-scan non-destructive testing (NDT) device. The probe performs an array scan of the impacted area at a preset scanning step size. By analyzing the reflected echo signals of ultrasonic waves at the material interface, the projected area of ​​interlaminar delamination damage caused by the impact inside the pipe is calculated and recorded.

[0083] Connect the pipe fittings that have completed non-destructive testing to the hydrostatic burst testing system, and seal all flange ports using high-pressure blind flanges. Inject water into the pipe fittings and purge the air, then slowly pressurize at a constant pressure increase rate of 1.0 MPa / min. When the pipe fittings experience internal pressure instability and leakage or pipe wall rupture and burst, the testing system automatically records the highest pressure peak value, which is taken as the residual burst pressure of the sample after impact.

[0084] Table 5. Test data of drop hammer impact damage and residual bearing capacity in Example 1 and Comparative Examples 1-3 Summarize: Figure 5 (a) The short black lines and square marks in the diagram represent the projected area of ​​internal damage in each experimental subject; Figure 5 (b) The black dotted lines and circles in the diagram represent the residual pressure values ​​of the corresponding samples, and the horizontal axis corresponds to the four independent experimental objects.

[0085] According to Table 5 and Figure 5 The data shows that the measured lesion area on ultrasound C-scan in Comparative Example 1 was 385.4 mm. 2 The residual burst pressure after impact was 11.3 MPa, with the largest damaged area and the lowest residual pressure-bearing capacity among the four groups of samples. In engineering construction and maintenance environments, pipe fittings are frequently subjected to low-speed mechanical impacts such as flange blind plate falling off and tool impacts. The external load generated by the collision extends into the material in the form of stress waves. The sample of Comparative Example 1 was assembled by gluing a straight pipe with a hole and then a branch pipe. A layer of pure resin of uneven thickness accumulated in the structural junction area. When the drop hammer impacts this area, the pure resin layer structure lacks the bridging effect of the fiber skeleton and is unable to effectively buffer the instantaneous interlaminar shear force.

[0086] Stress waves are reflected and superimposed at interfaces where the acoustic impedance of the material changes abruptly, inducing micro-cracks in the bonding surface and causing them to extend laterally in all directions. This leads to large-area matrix cracking and delamination, becoming severe stress concentration points highly susceptible to failure. This damage to structural continuity reduces the pipe wall's ability to withstand hydrostatic pressure, causing the pipe fitting to leak earlier during hydrostatic testing. The damaged area obtained in Example 1 was 142.6 mm². 2The residual burst pressure was recorded as 25.1 MPa. Based on the integrated co-curing molding mechanism, the carbon fiber bundles maintained a three-dimensional interlocking structure at the T-junction. During an impact event, the continuously extending fiber network conducted local mechanical kinetic energy along different directions, and the slight plastic deformation of the resin matrix, combined with the stretching of the fiber bundles, shared the external load, limiting the expansion of interlaminar cracking. Even after localized damage, the component maintained a relatively intact mechanical framework, upholding the required bearing capacity.

[0087] By combining the comparative data from the two sets of integral molding, it can be found that the parameter settings of the molding process have a specific influence on the material's resistance to impact damage. Comparative Example 2, due to the absence of a low-viscosity leveling process, recorded an impact damage area of ​​256.8 mm. 2 The residual burst pressure was 18.9 MPa. Incomplete impregnation of the high-viscosity resin left dry spots within the layup, which became structurally weakened areas under mechanical impact. The carbon fiber bundles, no longer encapsulated by the matrix, were more prone to localized buckling and fracture under longitudinal loads. In Comparative Example 3, due to insufficient vacuum system exhaust, the measured damage area was 221.3 mm². 2 The residual pressure was 20.4 MPa. The micropores remaining inside the material constituted internal stress concentration sources. Impact energy was more easily converted into interlaminar forces that tore the material around the pores, exacerbating the separation and spalling of the material interface.

[0088] This series of data distributions shows that, in the face of complex industrial field service requirements, the impact damage tolerance of composite pipe fittings depends not only on the spatial layout of continuous fibers in the region, but also on the constraints of the multi-stage exhaust leveling curing process. The combination of structural design and micro-density that controls porosity to an extremely low level jointly ensures the mechanical reliability of the overall component.

Claims

1. A method for preparing a high-strength integrated carbon fiber composite flange tee, characterized in that, Includes the following steps: Clean and polish the inner surface of the metal mold; The main body is laid in the metal mold. Carbon fiber prepreg with a fiber mass content of 58% to 62% is used as the laying material for the middle section of the straight pipe section and the middle section of the branch pipe of the flange tee. Carbon fiber prepreg with a fiber mass content of 58% to 65% is used as the laying material for the flange part of the flange tee. The materials are laid alternately. On this basis, reinforcement is carried out by laying an additional layer of unidirectional carbon fiber prepreg with a fiber mass content of 62% to 65% at the straight pipe section side opening connection section, the flange and straight pipe connection section, and the flange and branch pipe connection section. Before mold closing, a closed cavity is made, and the metal mold is vacuumed. The vacuum degree is controlled between -105kPa and -95kPa, and the vacuuming time is 19 to 21 minutes. The metal mold is placed in an autoclave for heating and pressurization to form and solidify in one piece using a multi-stage heating process. Then, heating is stopped, and the cooling rate is controlled at 0.5–1.0 °C / min to cool the metal mold to room temperature. The solidified flange tee is demolded and trimmed, the flange sealing surface is plasma-modified, and the flange bolt holes are machined.

2. The method for preparing a high-strength integrated carbon fiber composite flange tee according to claim 1, characterized in that, Both the carbon fiber prepreg and the unidirectional carbon fiber prepreg are T300-3K carbon fiber prepregs. When laying the main body, the carbon fiber prepreg used as the laying material for the middle section of the straight pipe and the middle section of the branch pipe has a fiber mass content of 60%. The carbon fiber prepreg used as the laying material for the flange portion has a fiber mass content of 62%.

3. The method for preparing a high-strength integrated carbon fiber composite flange tee according to claim 1, characterized in that, The side opening of the straight pipe section is the connection point between the branch pipe and the main straight pipe. The additional unidirectional carbon fiber prepreg has a fiber mass content of 63%.

4. The method for preparing a high-strength integrated carbon fiber composite flange tee according to claim 1, characterized in that, The metal mold is an integrally detachable metal mold with a one-piece molding structure. After cleaning the inner surface of the metal mold and before polishing, the process includes sequentially applying a release agent and a release wax to the inner surface of the metal mold; the polishing specifically refers to polishing to a mirror finish with a roughness Ra of 0.8 μm.

5. The method for preparing a high-strength integrated carbon fiber composite flange tee according to claim 1, characterized in that, When performing the alternating laying, specifically, 0° / 90° and 45° / -45° prepregs are laid alternately to the designed thickness, with the fiber direction deviation controlled within ±2°. Each layer is compacted using a rolling tool during the laying process.

6. The method for preparing a high-strength integrated carbon fiber composite flange tee according to claim 1, characterized in that, When creating the enclosed cavity, specifically after the lower mold is laid out but before the mold is closed, sealing strips, breathable felt, and vacuum bags are used to create the enclosed cavity.

7. The method for preparing a high-strength integrated carbon fiber composite flange tee according to claim 1, characterized in that, The process parameters for the vacuuming process are as follows: The laid metal mold is vacuumed using a vacuum pump, with the vacuum level controlled at -100 kPa for 20 minutes to completely remove residual air and low-molecular-weight volatiles between the layers.

8. The method for preparing a high-strength integrated carbon fiber composite flange tee according to claim 1, characterized in that, During the integrated heating and pressurizing molding and curing process, the metal mold is placed in the autoclave at room temperature. The specific parameters of the multi-stage heating process are as follows: The first stage involves raising the temperature to 88–92°C at a rate of 2.0–2.4°C / min and maintaining it at a pressure of 240–260 kPa for 1.9–2.1 hours. In the second stage, the temperature is increased to 128–132°C at a rate of 0.8–1.2°C / min and maintained at a pressure of 590–610 kPa for 3.9–4.1 hours.

9. The method for preparing a high-strength integrated carbon fiber composite flange tee according to claim 8, characterized in that, The specific parameters of the multi-stage heating process are as follows: The first stage involves heating to 90℃ at a rate of 2.0℃ / min and maintaining the temperature at 250kPa for 2.0 hours. In the second stage, the temperature is increased to 130℃ at a heating rate of 1.0℃ / min and maintained at 600kPa pressure for 4.0 hours.

10. The method for preparing a high-strength integrated carbon fiber composite flange tee according to claim 1, characterized in that, The specific implementation methods for demolding and trimming are as follows: The edges, side openings, and flange connection surfaces of the flange pipe tee are trimmed using cutting tools, and the surfaces are polished in sequence with 200-grit, 400-grit, and 600-grit sandpaper.